Preparation of Iron-Sulphur Alloys for Desulphurisation Studies - Sunderland, Malcolm (My University, 1967)
A levitation apparatus has been constructed for investigating the behaviour of liquid iron drops containing sulphur, whilst suspended in a moving gas stream.
To further this investigation, a source of iron-sulphur alloys, in form and size suitable for levitation, was required. Four methods for the preparation of the desired alloys were suggested, and each was experimentally examined in sequence.
The first 2 methods involved the quenching of a liquid solution of sulphur in iron, to give a solid alloy. The well-known behaviour of sulphur, to segregate on solidification, was observed, and the non-uniformity of the resulting alloys could not be tolerated. The third method involved preparing a large number of individual iron-sulphur samples by allowing drops of iron to fall and quench on particles of sulphur or iron sulphide. The repeatability of the method was found to be unsatisfactory. In the final attempt a levitated liquid drop of iron was equilibrated in a gas mixture of hydrogen-hydrogen sulphide. This method was considered more successful than the earlier three, and has the advantage that the prepared alloy drop is levitated and at the desired temperature.
Keywords: iron, sulphur, alloys, desulphurisation, gas stream, temperature, hydrogen